ORGANIZATIONAL CULTURE MAPPING USING ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT (OCAI) AT PT NEW RATNA MOTOR (NASMOCO) SEMARANG - Adriana, Luh Titisari Dewi; Perdhana, Mirwan Surya (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
This study was carried out to determine the current organizational culture at PT. New Ratna Motor (Nasmoco) Semarang, as well as the organizational culture that is expected in the next two years at PT. New Ratna Motor (Nasmoco), and to formulate the appropriate recommendations to achieve the expected organizational culture at PT. New Ratna Motor (Nasmoco) Semarang. The research was done by data collecting method such as questionnaire, observation and literature study. Meanwhile, the OCAI instrument is used for analysis, with respondents requested to complete a questionnaire about current organizational culture and organizational culture over the next two years (which is expected). The respondents in this research were 50 persons from PT. New Ratna Motor (Nasmoco) Semarang employees. Based on the study's findings, it was discovered that leaders and employees share the belief that the dominant organizational culture at PT. New Ratna Motor (Nasmoco) Semarang right now is a clan culture, while the leadership anticipates a decline in clan and an increase in market culture over the next two years.